Preoperative immune checkpoint inhibition and cryoablation in early-stage breast cancer - Comen, Elizabeth; Budhu, Sadna; Elhanati, Yuval; Page, David; Rasalan-Ho, Teresa; Ritter, Erika; Wong, Phillip; Plitas, George; Patil, Sujata; Brogi, Edi; Jochelson, Maxine; Bryce, Yolanda; et al. (iScience, 2024)
Local cryoablation can engender systemic immune activation/anticancer responses in tumors otherwise resistant to immune checkpoint blockade (ICB). We evaluated the safety/tolerability of preoperative cryoablation plus ipilimumab and nivolumab in 5 early-stage/resectable breast cancers. The primary endpoint was met when all 5 patients underwent standard-of-care primary breast surgery undelayedly. Three patients developed transient hyperthyroidism; one developed grade 4 liver toxicity (resolved with supportive management). We compared this strategy with cryoablation and/or ipilimumab. Dual ICB plus cryoablation induced higher expression of T cell activation markers and serum Th1 cytokines and reduced immunosuppressive serum CD4+PD-1hi T cells, improving effector-to-suppressor T cell ratio. After dual ICB and before cryoablation, T cell receptor sequencing of 4 patients showed increased T cell clonality. In this small subset of patients, we provide preliminary evidence that preoperative cryoablation plus ipilimumab and nivolumab is feasible, inducing systemic adaptive immune activation potentially more robust than cryoablation with/without ipilimumab. [Display omitted] •Preoperative cryoablation plus ipilimumab and nivolumab is feasible in breast cancer•This therapy induces systemic adaptive immune activation in patients•This therapy is potentially more robust than cryoablation with/without ipilimumab Health sciences; Oncology; Immunology